A missense point mutation in COL10A1 identified with whole-genome deep sequencing in a 7-generation Pakistan dwarf family. (January 2018) - Zhang, Chao; Liu, Jiaojiao; Iqbal, Furhan; Lu, Yan; Mustafa, Saima; Bukhari, Firdous; Lou, Haiyi; Fu, Ruiqing; Wu, Zhendong; Yang, Xiong; Bukhari, Ihtisham; Aslam, Muhammad; et al.
Abstract Disease-associated variants in the human genome are continually being identified using DNA sequencing technologies that are especially effective for Mendelian disorders. Here we sequenced whole genome to high coverage (>30×) of 6 members of a 7-generation family with dwarfism from a consanguineous tribe in Pakistan to determine the causal variant(s). We identified a missense variantrs111033552 (c.2011T>C [p.Ser671Pro]) located inCOL10A1 (encodes the alpha chain of type X collagen) as the most likely contributor to the dwarfism. We further confirmed the variant in 22 family members using Sanger sequencing. All affected individuals are heterozygous for the missense mutationrs111033552 and no individual homozygous was observed. Moreover, the mutation was absent in 69, 985 individuals representing >150 global populations. Taking advantage of whole-genome sequencing data, we also examined other variant forms, including copy number variation and insertion/deletion, but failed to identify such variants enriched in the affected individuals. Thusrs111033552 had priority for linkage with dwarfism.